Does Physiotherapy improve Physical Function, Kinesiophobia, and Quality of Life in Individuals with Back, Knee, and Ankle Problems?. (2022) - Fuhad, Aslinda; Zahari, Zarina; Justine, Maria; Purnomo, Didik
No abstract available